1985
DOI: 10.1111/j.1574-6968.1985.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of bacterial 5-enolpyruvylshikimate-3-phosphate synthases to the herbicide glyphosate

Abstract: The potent inhibition of the shikimate pathway enzyme 5‐enolpyruvylshikimate‐3‐phosphate (EPSP) synthase by the broad‐spectrum herbicide glyphosate (N‐[phosphonomethyl]glycine) was confirmed for the enzymes extracted from various bacteria, a green alga and higher plants. However, 5 out of 6 species belonging to the genus Pseudomonas were found to have EPSP synthases with a 50‐ to 100‐fold decreased sensitivity to the inhibitor. Correspondingly, growth of these 5 species was not inhibited by 5 mM glyphosate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Different extents of inhibition of EPSP synthase were reported previously for different Pseudomonas species (Schulz et al, 1985). Specifically, at about 3.0 µM glyphosate, there was 50% inhibition of the enzyme activity in P. fluorescens AFT36 but no inhibition in P. putida W1616 (Schulz et al, 1985). At one order of magnitude higher concentration (3 mM) of glyphosate, there was 100% inhibition of EPSP synthase in P. fluorescens AFT36 but only 50% inhibition in P. putida W1616 (Schulz et al, 1985).…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Different extents of inhibition of EPSP synthase were reported previously for different Pseudomonas species (Schulz et al, 1985). Specifically, at about 3.0 µM glyphosate, there was 50% inhibition of the enzyme activity in P. fluorescens AFT36 but no inhibition in P. putida W1616 (Schulz et al, 1985). At one order of magnitude higher concentration (3 mM) of glyphosate, there was 100% inhibition of EPSP synthase in P. fluorescens AFT36 but only 50% inhibition in P. putida W1616 (Schulz et al, 1985).…”
Section: Introductionmentioning
confidence: 88%
“…A decreased abundance in Pseudomonas species was reported in greenhouse soils wherein glyphosate was applied to soybeans in a manner similar to agricultural applications (Zobiole et al, 2011). Furthermore, a previous study revealed greater inhibition of the EPSP synthase activity in P. fluorescens AFT36 than in P. putida W1616 at the same glyphosate concentration (Schulz et al, 1985). We hypothesize that the sensitivity of glyphosate-exposed Pseudomonas species in glyphosate-containing soils could be due to (1) speciesspecific growth responses to glyphosate exposure, (2) glyphosate inhibition of the biosynthetic pathway for aromatic AAs, or (3) disruption of other cellular pathways.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations